CHURCH AND MISSION: THE NEW WAY MISSION AT 4.0 ERA - Zega, Ingati; Eko Susanto; Antonius Sugiharto; Vicky Paat (Jurnal Matetes STT Ebenhaezer, 2023)
Since the inception of the church at the day of Pentecost, the church has gone through world history for more than 2000 years and has experienced phase by phase of world development which has an impact on significant changes and reforms that affect the existence of the church. Now the church with all mankind has existed in the industrial era 4.0. In this era, human civilization is at an extraordinary level. The church also cannot deny the great influence of world developments in the 4.0 era on the church's call to the world. The church is faced with a number of great challenges to continue to carry out God's mission well. Although the implementation of the mission does not always run without obstacles, however, the mission has developed through various situations and conditions of mankind. So through this paper we will see how the church and mission in the 4.0 era so that the church can mission in a new way according to developments in the 4.0 era without losing the essence of the mission and the church. Of course the church also experiences many challenges when on a mission in the 4.0 era, so the church must strive to develop a strategy in mission service in the 4.0 era by navigating a new landscape in mission service in the 4.0 era, so that the church is able to build a movement in mission service in the 4.0 era and synergize with ecclesiastical institutions in carrying out missio dei in the world.